Reduction of flavonoid content in honeysuckle via Erysiphe lonicerae-mediated inhibition of three essential genes in flavonoid biosynthesis pathways - Zhang, Mian; Zhang, Jie; Xiao, Qiaoqiao; Li, Yulong; Jiang, Shanshan (Frontiers in Plant Science, 2024)
Honeysuckle, valued for its wide-ranging uses in medicine, cuisine, and aesthetics, faces a significant challenge in cultivation due to powdery mildew, primarily caused by the Erysiphe lonicerae pathogen. The interaction between honeysuckle and E. lonicerae, especially concerning disease progression, remains insufficiently understood. Our study, conducted in three different locations, found that honeysuckle naturally infected with E. lonicerae showed notable decreases in total flavonoid content, with reductions of 34.7%, 53.5%, and 53.8% observed in each respective site. Controlled experiments supported these findings, indicating that artificial inoculation with E. lonicerae led to a 20.9% reduction in flavonoid levels over 21 days, worsening to a 54.8% decrease by day 42. Additionally, there was a significant drop in the plant' s total antioxidant capacity, reaching an 81.7% reduction 56 days after inoculation. Metabolomic analysis also revealed substantial reductions in essential medicinal components such as chlorogenic acid, luteolin, quercetin, isoquercetin, and rutin. Investigating gene expression revealed a marked decrease in the relative expression of the LjPAL1 gene, starting as early as day 7 post-inoculation and falling to a minimal level (fold change = 0.29) by day 35. This trend was mirrored by a consistent reduction in phenylalanine deaminase activity in honeysuckle through the entire process, which decreased by 72.3% by day 56. Further analysis showed significant and sustained repression of downstream genes LjFNHO1 and LjFNGT1, closely linked to LjPAL1. We identified the mechanism by which E. lonicerae inhibits this pathway and suggest that E. lonicerae may strategically weaken the honeysuckle's disease resistance by targeting key biosynthetic pathways, thereby facilitating further pathogen invasion. Based on our findings, we recommend two primary strategies: first, monitoring medicinal constituent levels in honeysuckle from E. lonicerae-affected areas to ensure its therapeutic effectiveness; and second, emphasizing early prevention and control measures against honeysuckle powdery mildew due to the persistent decline in crucial active compounds.